Eco-friendly polishing pad and manufacturing method thereof

JP2025029573AActive Publication Date: 2025-03-06SK ENPULSE CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2024102147
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-19
Filing Date
2024-06-25
Publication Date
2025-03-06
Estimated Expiration
2044-06-25

AI Technical Summary

Benefits of technology

【0013】 前記実施例による研磨パッドは、バイオマス原料を含む組成物を用いて製造されながらも、バイオマス原料の成分および含有量などを調整して、研磨パッドに含まれるバイオマス含有量を特定の範囲内に制御したものであって、これにより、環境配慮性に優れるとともに、CMP工程において好適な硬度、モジュラス、引張強度、および伸び率のような物性を有し、研磨率や切削率もなお優れる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029573000001_ABST
    Figure 2025029573000001_ABST
Patent Text Reader

Abstract

To provide an eco-friendly polishing pad and a manufacturing method thereof.SOLUTION: The present invention relates to an eco-friendly polishing pad and a manufacturing method thereof. The polishing pad manufactured from a polyurethane resin including a bio-based polymer polyol has excellent eco-friendliness and has physical properties such as hardness and modulus required for a CMP process. Thus, it can be used in the manufacture of semiconductor substrates to demonstrate excellent performance.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The embodiment relates to a polishing pad used in the chemical mechanical planarization (CMP) process of semiconductor devices, and more particularly to an environmentally friendly biomass-based polishing pad and a method for manufacturing the same. [Background technology]

[0002] In the semiconductor manufacturing process, the chemical mechanical polishing (CMP) process is a process in which a semiconductor substrate such as a wafer is attached to a head and brought into contact with the surface of a polishing pad fixed on a platen, and the platen and the head are moved relative to each other to flatten uneven portions of the semiconductor substrate surface.

[0003] In such a CMP process, the polishing pad is required to have stable physical properties since it has a large effect on the surface processing quality of the semiconductor substrate. In particular, since the polishing rate of the CMP process can be sensitively changed depending on the components contained in the polishing pad and their physical properties, it is necessary to optimize the components contained in the polishing pad and their physical properties.

[0004] On the other hand, with the recent occurrence of environmental problems such as climate change, public opinion is forming that companies should take on social responsibility for building a sustainable society through ESG (Environment, Social, Governance) management such as carbon neutrality. As a result, various companies are attempting to manufacture a variety of products by applying biomass raw materials derived from plants, etc., instead of petroleum-based raw materials.

[0005] In line with this trend, it is necessary to try to improve environmental friendliness by using biomass raw materials for polishing pads that have been manufactured using petroleum-based raw materials. Furthermore, it is necessary to provide a polishing pad that has physical properties that allow it to achieve the level of removal rate required in the CMP process even when the biomass raw materials are used. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Republic of Korea Patent Publication No. 2018-0044771 Summary of the Invention [Problem to be solved by the invention]

[0007] An example of this would be to provide a polishing pad that is environmentally friendly and exhibits performance such as the polishing rate required in the CMP process.

[0008] Also, the embodiment provides a method for manufacturing a polishing pad that can efficiently manufacture the polishing pad. [Means for solving the problem]

[0009] According to one implementation, a polishing pad is provided that includes a polishing layer, the polishing layer including a polyurethane resin, the polyurethane resin including a polyol and a polyisocyanate, and the polyol including a bio-based polymer polyol.

[0010] According to another embodiment, a method for producing a polishing pad is provided, comprising preparing a urethane prepolymer comprising a polyol and a polyisocyanate, and curing the urethane prepolymer to produce a polishing layer comprising a polyurethane resin, the polyol comprising a bio-based polymer polyol.

[0011] A polishing pad according to another implementation includes a polishing layer including a polyurethane resin, the polyurethane resin including a polyol component and a polyisocyanate component, the polyol component including a bio-based polymer polyol and a bio-based monomer polyol.

[0012] Another embodiment of a method for manufacturing a polishing pad includes preparing a bio-based urethane prepolymer using a polyurethane resin including a polyol component and a polyisocyanate component, and curing the bio-based urethane prepolymer to produce a polishing layer, the polyol component including a bio-based polymer polyol and a bio-based monomer polyol. Effect of the Invention

[0013] The polishing pad according to the above embodiment is manufactured using a composition containing a biomass raw material, but the components and content of the biomass raw material are adjusted to control the biomass content in the polishing pad within a specific range. As a result, it is environmentally friendly and has physical properties such as hardness, modulus, tensile strength, and elongation that are suitable for the CMP process, and also has excellent polishing and cutting rates.

[0014] In addition, the polishing pad according to the embodiment includes a polishing layer containing a polyurethane resin, the polyurethane resin including a polyol component and a polyisocyanate component, and the polyol component including a bio-based polymer polyol and a bio-based monomer polyol, and therefore is environmentally friendly and has the physical properties required for the CMP process, and can be used in the manufacture of semiconductor substrates to demonstrate excellent performance.

[0015] Therefore, when a CMP process is performed using a polishing pad according to the embodiment, a semiconductor substrate such as a wafer exhibits a high polishing rate and has excellent surface processing quality. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 shows a 13C-NMR spectrum of an abrasive layer according to one embodiment. [Diagram 2] FIG. 2 shows the 13C-NMR spectrum of an abrasive layer according to another embodiment. [Diagram 3] FIG. 3 illustrates a cross-sectional view of a polishing pad according to one implementation. [Figure 4] FIG. 4 illustrates a semiconductor device manufacturing process using a polishing pad according to one implementation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] In the following description of the implementation examples, if a detailed description of related known configurations or functions is determined to make the gist of the implementation example unclear, the detailed description will be omitted. In addition, the size of each component in the drawings may be exaggerated or omitted for the purpose of explanation, and may differ from the size actually applied.

[0018] In this specification, a description that one component is formed above / below another component, or is connected or joined to each other includes being formed, connected or joined directly between these components, or indirectly through other components. It should be understood that the reference regarding the above / below of each component may change depending on the direction in which the object is observed.

[0019] In this specification, the terms referring to each component are used to distinguish it from other components and are not intended to limit the implementation examples. Furthermore, in this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise.

[0020] In this specification, the terms "first", "second", etc. are used to describe various components, and the components should not be limited by the terms. The terms are used for the purpose of distinguishing one component from another.

[0021] In this specification, when a part is said to "comprise" a certain component, this does not mean that it excludes other components, but that it may further include other components, unless specifically stated to the contrary.

[0022] The molecular weight of the compounds and polymers described herein is conveniently expressed in units of molar mass, but may be understood as a relative mass based on carbon 12. The molecular weight of the polymers described herein may be interpreted as a water-average molecular weight or a weight-average molecular weight, for example, as a water-average molecular weight.

[0023] All numerical ranges indicating physical properties, dimensions, and the like of components described herein can be understood to be modified in all cases by the term "about" unless otherwise specified.

[0024] In the numerical ranges limiting the size, physical properties, etc. of the components described in this specification, when a numerical range limited only by an upper limit value and a numerical range limited only by a lower limit value are separately exemplified, it should be understood that the numerical range combining these upper and lower limits is also included in the exemplary range.

[0025] In this specification, the term "bio-based" refers to a component that is not based on fossil fuels such as petroleum, but is obtained in whole or in part from biomass derived from plants or other sources. Specifically, the component does not contain fossil fuel-based materials such as petroleum, but contains carbon-14 ( 14 C).

[0026] For example, "bio-based polyol" means a polyol obtained in whole or in part from biomass derived from plants, etc., and does not contain radioactive carbon ( 14 C), and thus can be distinguished from polyols obtained from fossil fuel-based materials, which do not contain this.

[0027] The term "biomass" broadly refers to a concept that encompasses biological materials such as animal and plant resources, such as trees, flowers, corn, sugarcane, grass, whale oil, algae, etc., or organic waste resources, such as livestock manure, food waste, and sawdust, etc. 14 C).

[0028] [Polishing pad] A polishing pad according to one implementation includes a polishing layer, the polishing layer including a polyurethane resin, the polyurethane resin including a polyol and a polyisocyanate, and the polyol including a bio-based polymer polyol.

[0029] A polishing pad according to another implementation includes a polishing layer including a polyurethane resin, the polyurethane resin including a polyol component and a polyisocyanate component, the polyol component including a bio-based polymer polyol and a bio-based monomer polyol.

[0030] The polyurethane resin in the polishing layer is prepared from a urethane prepolymer containing a polyol and a polyisocyanate, and more specifically, may be prepared from a composition containing the urethane prepolymer, a curing agent, and a foaming agent.

[0031] <Bio-based polymer polyol> According to one implementation, the polyurethane resin includes a polyol component, and the polyol component includes a bio-based polymer polyol.

[0032] The bio-based polymer polyol is derived from biomass and is a radioactive carbon isotope, carbon-14( 14 C) a polymer polyol having 2 or more hydroxyl groups (OH) and may have 2 or more, 5 or more, or 10 or more repeat units.

[0033] Specifically, the bio-based polymer polyol may include one or more selected from the group consisting of bio-based polyether polyols, bio-based polyester polyols, bio-based polycarbonate polyols, and bio-based polycaprolactam polyols.

[0034] When the properties of the bio-based polymer polyol, such as the molecular weight, hydroxyl value (OH-value), and functionality, are adjusted within a certain range, it may be more advantageous to provide a polishing pad with better flexibility, elastic recovery, permanent deformation rate, weather resistance, hydrolysis resistance, and the like.

[0035] In addition, in order to improve the properties of the polishing pad, such as flexibility, elastic recovery, permanent deformation rate, weather resistance, and hydrolysis resistance, it is important to control the properties of the bio-based polymer polyol, such as the weight average molecular weight, hydroxyl value, and number of functional groups.

[0036] For example, the molecular weight of the bio-based polymer polyol can be 300 g / mol or more, 400 g / mol or more, 450 g / mol or more, 500 g / mol or more, 600 g / mol or more, 700 g / mol or more, or 800 g / mol or more, and 5000 g / mol or less, 4000 g / mol or less, 3000 g / mol or less, 2700 g / mol or less, 2300 g / mol or less, 1800 g / mol or less, 1500 g / mol or less, or 1200 g / mol or less.

[0037] As a specific example, the bio-based polymer polyol may have a molecular weight of 400 g / mol to 3000 g / mol.

[0038] More specifically, the molecular weight of the bio-based polymer polyol can be 450 g / mol to 2700 g / mol, 500 g / mol to 2300 g / mol, 600 g / mol to 1800 g / mol, 700 g / mol to 1500 g / mol, or 800 g / mol to 1200 g / mol.

[0039] The hydroxyl value of the bio-based polymer polyol may be, for example, 35 mgKOH / g or more, 45 mgKOH / g or more, 60 mgKOH / g or more, 70 mgKOH / g or more, 80 mgKOH / g or more, or 90 mgKOH / g or more, and may be 250 mgKOH / g or less, 230 mgKOH / g or less, 200 mgKOH / g or less, 180 mgKOH / g or less, 150 mgKOH / g or less, or 130 mgKOH / g or less.

[0040] In one specific example, the bio-based polymer polyol may have a hydroxyl value of 35 mg KOH / g to 250 mg KOH / g.

[0041] More specifically, the hydroxyl value of the bio-based polymer polyol can be 45 mgKOH / g to 230 mgKOH / g, 60 mgKOH / g to 200 mgKOH / g, 70 mgKOH / g to 180 mgKOH / g, 80 mgKOH / g to 150 mgKOH / g, 90 mgKOH / g to 130 mgKOH / g, or 100 mgKOH / g to 125 mgKOH / g.

[0042] The number of functional groups of the bio-based polymer polyol may be 2 or more or 3 or more, and may be 10 or less, 5 or less, 4 or less, or 3 or less. More specifically, the number of functional groups of the bio-based polymer polyol may be 2 to 4.

[0043] Examples of commercially available bio-based polymer polyols include ECOTRION® H2000 and ECOTRION H1000 from SK Chemicals, BI-550 and B-1184 from SK pucore; Sovermol® 1102, Sovermol 1005, Sovermol 805, and Sovermol 815 from BASF; BP-04 and BP-05 from NOROO; Priplast® 2033 and Priplast 1838 from Croda; Velvetol H500, Velvetol H1000, Velvetol H2000, and Velvetol H2700 from ALLESSA; or combinations thereof.

[0044] The biomass content in the bio-based polymer polyol can be, for example, 10% by weight or more, 20% by weight or more, 30% by weight or more, 50% by weight or more, 60% by weight or more, 70% by weight or more, or 80% by weight or more, and can be 100% by weight or less, 90% by weight or less, or 85% by weight or less.

[0045] More specifically, the biomass content based on the total weight of the bio-based polymer polyol is 20% by weight to 100% by weight, and may be 40% by weight to 100% by weight, 50% by weight to 100% by weight, 60% by weight to 100% by weight, 70% by weight to 100% by weight, or 80% by weight to 100% by weight. When the biomass content of the bio-based polymer polyol satisfies the above range, a polishing pad having properties required in the CMP process and further excellent environmental friendliness can be provided.

[0046] The biomass content may be a value measured based on the ASTM D 6866 standard, which is a standard analytical method for measuring the biomass content of a solid, liquid, or gas sample using radiometric dating or Accelerator Mass Spectrometry (AMS) methods.

[0047] The radiocarbon dating method may include the following steps. Specifically, a pre-treated (e.g., foreign matter removed) sample is placed in a special vacuum device and burned to produce carbon dioxide. Molten lithium is then mixed with the sample to produce lithium carbide, which is then cooled and reacted with water to produce acetylene gas. The acetylene gas is then purified and converted to benzene using a silica-alumina catalyst. The 92% carbon benzene is then mixed with scintillation chemicals and radioactivity is measured using a liquid scintillation counter for about two days.

[0048] The acceleration mass spectrometry method may include the following steps: A sample (test piece) that has been pretreated (e.g., foreign matter removed) is burned to produce purified carbon dioxide, which is then reacted with hydrogen in a special glass vacuum chamber to produce graphite. The 100% carbon graphite is then placed in an acceleration mass analyzer and radioactivity is measured for about 30 minutes.

[0049] <Bio-based monomer polyol> According to one implementation, the polyurethane resin includes a polyol component, and the polyol component includes a bio-based monomer polyol.

[0050] Specifically, the polyurethane resin may further include one or more bio-based monomer polyols. More specifically, the polyurethane resin may be prepared from a composition including one or more bio-based monomer polyols.

[0051] Thereby, the polyurethane resin can contain repeating units derived from the bio-based monomer polyol as well as repeating units derived from the bio-based polymer polyol.

[0052] The bio-based monomer polyol is derived from biomass and is a radioactive carbon isotope, carbon-14( 14 The monomolecular polyol containing C) has two or more hydroxyl groups (OH).

[0053] By including both the bio-based polymer polyol and the bio-based monomer polyol, the crosslink density of the urethane prepolymer can be improved, and the hardness, durability, etc. required for the CMP process can be ensured.

[0054] More specifically, in consideration of the weight average molecular weight and the chain length, the bio-based monomer polyol may be most preferably bio-based 1,3-propanediol, but is not limited thereto.

[0055] The biobased monomer polyol may comprise one or more selected from the group consisting of biobased ethylene glycol, biobased diethylene glycol, biobased 1,2-propylene glycol, biobased 1,3-propanediol, biobased 2-methyl-1,3-propanediol, biobased 1,3-butanediol, biobased 1,4-butanediol, biobased 2,3-butanediol, biobased 1,5-pentanediol, biobased 1,9-nonanediol, biobased 1,10-decanediol, and biobased isosorbide.

[0056] More specifically, the bio-based monomer polyol may include one or more selected from the group consisting of bio-based 1,3-propanediol, bio-based 1,3-butanediol, bio-based 1,4-butanediol, bio-based 2,3-butanediol, bio-based 1,5-pentanediol, bio-based 1,9-nonanediol, bio-based 1,10-decanediol, and bio-based isosorbide.

[0057] The bio-based monomer polyol may have a weight average molecular weight of 50 g / mol to 200 g / mol. For example, the weight average molecular weight of the bio-based monomer polyol may be 55 g / mol to 180 g / mol, 60 g / mol to 150 g / mol, 65 g / mol to 130 g / mol, 70 g / mol to 100 g / mol, or 75 g / mol to 90 g / mol. When the weight average molecular weight of the bio-based monomer polyol is within the above range, a polishing pad having further excellent hardness, durability, etc. may be provided.

[0058] The bio-based monomer polyol may have a biomass content of 50% by weight or more, 80% by weight or more, 90% by weight or more, 80% by weight to 100% by weight or 85% by weight to 100% by weight, or more specifically 100% by weight, based on the total weight of the bio-based monomer polyol.

[0059] When the biomass content of the biomonomer polyol is within the above range, it may be more advantageous to provide a polishing pad that has the physical properties required in the CMP process and is also environmentally friendly.

[0060] The weight ratio of the bio-based polymer polyol to the bio-based monomer polyol may be 5 to 20:0.01 to 2. For example, the weight ratio of the bio-based polymer polyol to the bio-based monomer polyol may be 5 to 20:0.02 to 2, 5 to 18:0.05 to 2, 5 to 15:0.1 to 2, 8 to 20:0.2 to 2, or 8 to 15:0.5 to 1.5.

[0061] <Other polyols> The polyol contained in the polyurethane resin constituting the polishing layer may further contain a petroleum-based polyol in addition to the bio-based polyol.

[0062] Specifically, the polyol may further include one or more selected from the group consisting of petroleum-based polymer polyols and petroleum-based monomer polyols.

[0063] The petroleum-based polymer polyol may include one or more selected from the group consisting of commonly known polyether polyols, polyester polyols, polycarbonate polyols, and polycaprolactam polyols.

[0064] The petroleum-based monomer polyol may contain one or more selected from the group consisting of commonly known ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propanediol, 2-methyl-1,3-propanediol, dipropylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, n-butanol, isobutanol, 1,5-pentanediol, 1,6-hexanediol, 2-octanol, 1,9-nonanediol, and 1,10-decanediol.

[0065] When the polyol in the polyurethane resin contains both the bio-based polyol (a) and the petroleum-based polyol (b), the mixing ratio (a:b) therebetween may be a molar ratio of 1:0.65 to 1:3, a molar ratio of 1:0.65 to 1:1.5, a molar ratio of 1:0.65 to 1:1.25, a molar ratio of 1:0.65 to 1:0.92, a molar ratio of 1:0.68 to 1:0.90, a molar ratio of 1:0.72 to 1:0.88, a molar ratio of 1:0.75 to 1:0.86, or a molar ratio of 1:0.80 to 1:0.85.

[0066] Within the above range of mixing ratio, it is further advantageous to provide a polishing pad that has the physical properties required in the CMP process and is also environmentally friendly.

[0067] <Polyisocyanate> According to one implementation, the polyurethane resin can include a polyisocyanate.

[0068] Specifically, the polyisocyanate contained in the polyurethane resin constituting the polishing layer may include a commonly known polyisocyanate. For example, the polyisocyanate may include a petroleum-based polyisocyanate, but is not limited thereto.

[0069] Specifically, the polyisocyanate may include one or more selected from the group consisting of aromatic diisocyanates, aliphatic diisocyanates, and alicyclic diisocyanates. More specifically, the polyisocyanate may include one or more selected from the group consisting of aromatic diisocyanates and alicyclic diisocyanates.

[0070] For example, the polyisocyanate may include one or more selected from the group consisting of toluene diisocyanate (TDI), naphthalene-1,5-diisocyanate, p-phenylene diisocyanate, tolidine diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate, 4,4'-methylenedicyclohexyl diisocyanate (H12MDI), and isophorone diisocyanate.

[0071] Preferably, the polyisocyanate may include one or more of toluene diisocyanate (TDI) and 4,4'-methylenedicyclohexyl diisocyanate (H12MDI). When the polyisocyanate is included, a hard segment is formed, which may be more advantageous in providing a polishing pad with a desired level of hardness.

[0072] When the toluene diisocyanate (TDI) (x) and the 4,4'-methylenedicyclohexyl diisocyanate (H12MDI) (y) are used in combination, the mixing ratio (x:y) is not particularly limited, and may be specifically a weight ratio of 3:1 to 20:1, a weight ratio of 5:1 to 18:1, a weight ratio of 7:1 to 16:1, or a weight ratio of 8:1 to 13:1.

[0073] <Hardening agent and foaming agent> According to one embodiment, the polyurethane resin constituting the polishing layer may further include a curing agent and a foaming agent. The curing agent may include a compound that undergoes a curing reaction with a urethane prepolymer for preparing the polyurethane resin.

[0074] Specifically, the curing agent may include one or more selected from the group consisting of aromatic amines, aliphatic amines, aromatic alcohols, and aliphatic alcohols.

[0075] For example, the curing agent may include one or more selected from the group consisting of 4,4'-methylenebis(2-chloroaniline), diethyltoluenediamine, diaminodiphenylmethane, dimethylthio-toluene diamine, propanediolbis(p-aminobenzoate), diaminodiphenylsulfone, m-xylylenediamine, isophoronediamine, ethylenediamine, diethylenetriamine, triethylenetetramine, polypropylenediamine, polypropylenetriamine, and bis(4-amino-3-chlorophenyl)methane.

[0076] The foaming agent is for forming a pore structure in the abrasive layer, and may include one or more selected from the group consisting of solid-phase foaming agents, liquid-phase foaming agents, and gas-phase foaming agents (e.g., gases such as nitrogen, argon, helium, and carbon dioxide).

[0077] Specifically, the foaming agent may be a solid-phase foaming agent containing expandable particles. The expandable particles are particles that have the property of being expandable by heat, pressure, etc., and the size of the particles in the final polishing layer may be determined by the heat and pressure applied during the manufacturing process of the polishing layer. More specifically, the expandable particles may include thermally expanded particles, unexpanded particles, or a combination thereof.

[0078] The thermally expanded particles are particles that have been expanded in advance by heat, and may refer to particles whose final size is determined by expanding due to heat or pressure applied during the manufacturing process of the abrasive layer.

[0079] Such expandable particles may include an outer shell of a resinous material and an expansion-inducing component present within the outer shell.

[0080] The resinous outer shell may include a thermoplastic resin, which may be at least one selected from the group consisting of vinylidene chloride copolymers, acrylonitrile copolymers, methacrylonitrile copolymers, and acrylic copolymers.

[0081] The expansion-inducing component may include one or more selected from the group consisting of a hydrocarbon compound, a chlorofluoro compound, and a tetraalkylsilane compound.

[0082] Specifically, the hydrocarbon compound may include one or more selected from the group consisting of ethane, ethylene, propane, propene, n-butane, isobutene, n-butene, isobutene, n-pentane, isopentane, neopentane, n-hexane, heptane, and petroleum ether.

[0083] The chlorofluoro compound may include one or more selected from the group consisting of trichlorofluoromethane (CCl3F), dichlorodifluoromethane (CCl2F2), chlorotrifluoromethane (CClF3), and dichlorotetrafluoroethane (C2Cl2F4).

[0084] The tetraalkylsilane compound may include one or more selected from the group consisting of tetramethylsilane, trimethylethylsilane, trimethylisopropylsilane, and trimethyl-n-propylsilane.

[0085] The solid foaming agent has an average particle size of 5 μm to 200 μm, specifically 10 μm to 100 μm, 15 μm to 70 μm, or 20 μm to 45 μm. When the solid foaming agent is the expandable particles and contains the thermally expanded particles, the average particle size may mean the average particle size of the thermally expanded particles themselves. When the solid foaming agent is the expandable particles and contains the unexpanded particles, the average particle size may mean the average particle size of the particles after expansion by heat or pressure.

[0086] <Characteristics of the polishing layer> The thickness of the polishing layer may be 0.5 mm to 5 mm. For example, the thickness of the polishing layer may be 0.8 mm to 4 mm, 1 mm to 3 mm, 1.5 mm to 2.5 mm, 1.7 mm to 2.3 mm, or 2.0 mm to 2.2 mm. When the thickness of the polishing layer satisfies the above range, the particle size deviation between the upper and lower parts of the pores can be minimized, while the basic physical properties of the polishing pad can be sufficiently secured.

[0087] The hardness of the polishing layer may be 45 Shore D or more. For example, the hardness of the polishing layer may be 46 Shore D or more, 50 Shore D or more, 53 Shore D or more, or 56 Shore D or more, and 80 Shore D or less, 70 Shore D or less, 68 Shore D or less, 65 Shore D or less, or 60 Shore D or less.

[0088] As a specific example, the hardness of the abrasive layer may be 45 Shore D to 80 Shore D, 45 Shore D to 70 Shore D, 46 Shore D to 60 Shore D, 50 Shore D to 68 Shore D, 53 Shore D to 66 Shore D, 53 Shore D to 65 Shore D, 55 Shore D to 64 Shore D, 56 Shore D to 60 Shore D, or 56 Shore D to 62 Shore D.

[0089] The tensile strength of the polishing layer is 5N / mm 2 More than 10N / mm 2 More than 15N / mm 2 or more than 17N / mm 2 Above 30N / mm 2 Below, 28N / mm 2 Below, 27N / mm 2 Below, 26N / mm 2 Below, 25N / mm 2 Below, 23N / mm 2 or less than 20N / mm 2 It can be the following:

[0090] As a specific example, the tensile strength of the polishing layer is 5 N / mm 2 ~30N / mm 2 , 10N / mm 2 ~25N / mm 2 , 12N / mm 2 ~27N / mm 2 , 15N / mm 2 ~25N / mm 2 , 15N / mm 2 ~23N / mm 2 , 20N / mm 2 ~25N / mm 2 , 16N / mm 2 ~24N / mm 2 , 17N / mm 2~27N / mm 2 , or 18 N / mm 2 ~23N / mm 2 It could be.

[0091] The elongation of the polishing layer may be 50% or more, 70% or more, 90% or more, 106% or more, or 120% or more, and 300% or less, 250% or less, 200% or less, or 150% or less. As a specific example, the elongation of the polishing layer may be 50% to 300%, 60% to 150%, 62% to 120%, 80% to 200%, 90% to 130%, 85% to 120%, 85% to 115%, 95% to 110%, or 98% to 105%. The elongation may be the breaking elongation.

[0092] According to one embodiment, the abrasive layer has a hardness of 45 Shore D to 70 Shore D and a tensile strength of 15 N / mm 2 ~27N / mm 2 and the elongation rate may be 50% to 150%. Within the above range of properties of the abrasive layer, the performance such as the polishing rate and cutting rate during the CMP process may be further improved.

[0093] According to another embodiment, the polishing layer has a hardness of 55 Shore D to 64 Shore D and a tensile strength of 20 N / mm 2 ~25N / mm 2 The hardness, tensile strength and elongation of the polishing layer can be adjusted within the above ranges, whereby the CMP step can be performed stably and the weight of the polishing pad can be reduced.

[0094] In particular, by satisfying all of the properties of the polishing layer within the above ranges, the polishing rate and cutting rate as well as the polishing speed in the CMP process can be further improved. More specifically, by controlling the hardness and polishing rate of the polishing layer within the above ranges, an appropriate polishing rate in the CMP process of the polishing pad can be ensured, and by controlling the elongation rate of the polishing layer within the above ranges, defects such as brittleness and easy breakage or scars on the surface of the polished object can be effectively prevented.

[0095] Furthermore, the average size of pores formed in the polishing layer is not particularly limited, and may be specifically 10 μm to 40 μm, 15 μm to 35 μm, 18 μm to 30 μm, or 20 μm to 25 μm.

[0096] When the thickness, hardness and average pore size of the polishing layer are within the above ranges, the CMP process can be carried out more stably and the weight of the polishing pad can be reduced.

[0097] The biomass content of the polishing layer may be 2% to 70% by weight. For example, based on the total weight of the polishing layer, the biomass content of the polishing layer may be 3% to 65% by weight, 5% to 60% by weight, 6% to 58% by weight, 7% to 56% by weight, 8% to 54% by weight, 20% to 52% by weight, or 35% to 50% by weight.

[0098] Meanwhile, the polishing layer is a hardened product made of a compound having a specific chemical structure, and the final polishing performance, such as the polishing rate and the degree of defects, can be determined by the chemical structure of the compound and each bond structure and bond strength of the repeating units that make up the chemical structure. The compounds contained in the polishing layer include various forms of chemical bond structures, and when the polishing layer is treated under specific treatment conditions, the bonds are either separated or maintained depending on the bond strength of each bond structure. Thus, the carbon-13 nuclear magnetic resonance ( 13 The shape of the C-NMR spectrum may be different. 13 The shape of the C-NMR spectrum is a characteristic that is expressed in a comprehensive manner in which not only the components and contents used to manufacture the abrasive layer, but also the various process conditions during the manufacturing process of the abrasive layer and the processing conditions for obtaining the processing composition are organically related to each other.

[0099] For the polishing pad according to one embodiment, 1 g of the polishing layer was placed in a 0.3M potassium hydroxide (KOH) aqueous solution and reacted in a sealed container at 150°C for 48 hours. 13When a C-NMR spectrum is measured, it may include a first peak appearing at 28 ppm to 31 ppm; a second peak appearing at 31 ppm to 33 ppm; and a third peak appearing at 67 ppm to 71 ppm.

[0100] The polishing layer is made of a compound having a chemical bond structure corresponding to the spectral characteristics, which has the effect of improving the polishing performance of the polishing pad.

[0101] The ratio (p1 / p2) of the area of ​​the first peak (p1) to the area of ​​the second peak (p2) may be, for example, 2 or more, 3 or more, 4 or more, or 4.4 or more, and 8 or less, 7 or less, 6 or less, or 5.7 or less. As a specific example, the ratio of the area of ​​the first peak to the area of ​​the second peak may be 4.4 to 5.7.

[0102] Furthermore, the ratio (p3 / p2) of the area of ​​the third peak (p3) to the area of ​​the second peak (p2) may be 6 or more, 7 or more, 8 or more, or 8.2 or more, and may be 11 or less, 10 or less, 9 or less, or 8.8 or less. As a specific example, the ratio of the area of ​​the third peak to the area of ​​the second peak may be 8.2 to 8.8.

[0103] In one specific example, the area ratio of the first peak to the area of ​​the second peak may be 4.4 to 5.7, and the area ratio of the third peak to the area of ​​the second peak may be 8.2 to 8.8.

[0104] Within the above range of peak area ratio, the polishing layer exhibits appropriate hardness and elongation, and the polishing rate can be improved and defects can be reduced.

[0105] In particular, 13 The test composition obtained under the C-NMR test conditions, i.e., 1 g of the polishing layer was placed in a 0.3 M potassium hydroxide (KOH) aqueous solution and reacted in a sealed container at 150° C. for 48 hours, was compared with the test compositions prepared under other conditions. 13C-NMR spectrum showed results that were highly correlated with the polishing performance of the final polishing pad.

[0106] In the conditions for treating the polishing layer, the pressure in the closed vessel may be 3 bar or less, although it is not necessary to adjust the pressure to a specific condition, as a closed vessel is sufficient.

[0107] In addition, the polishing layer 13 The C-NMR spectrum may have further characteristic peaks in addition to the first peak to the third peak.

[0108] The polishing pad according to one embodiment is 13 When the C-NMR spectrum is measured, it may further include a fourth peak appearing at 33 ppm to 36 ppm; and a fifth peak appearing at 61 ppm to 63 ppm.

[0109] The polishing layer is made of a compound having a chemical bond structure corresponding to the spectral characteristic having the additional peak, which can have the effect of improving the polishing performance of the polishing pad.

[0110] The ratio (p4 / p5) of the area of ​​the fourth peak (p4) to the area of ​​the fifth peak (p5) may be, for example, 1 or more, 2 or more, or 2.1 or more, and may be 9 or less, 8 or less, 7 or less, or 6.4 or less.

[0111] In one specific example, the ratio of the area of ​​the fourth peak to the area of ​​the fifth peak may be 2.1 to 6.4.

[0112] Within the above range of peak area ratio, the polishing layer exhibits appropriate hardness and elongation, and the polishing rate can be improved and defects can be reduced.

[0113] The test composition of the polishing layer 13The shape of the C-NMR spectrum can be determined by a combination of factors such as the type and content of raw material monomers in the process of manufacturing the abrasive layer, process temperature and pressure conditions, and the type and content of additives such as curing agents and foaming agents.

[0114] <Other constituent layers> FIG. 3 is a diagram illustrating a cross section of a polishing pad according to one implementation. 3, a polishing pad 100 according to one implementation may include a polishing layer 10 as a top pad layer, and may further include a support layer 30 as a subpad layer under the polishing layer 10. The polishing pad 100 may further include an adhesive layer 20 between the polishing layer 10 and the support layer 30.

[0115] The adhesive layer is provided between the polishing layer and the support layer and serves to bond the polishing layer and the support layer. Furthermore, the adhesive layer may also serve to prevent the polishing slurry supplied to the polishing layer from flowing out to the support layer. Such an adhesive layer may be formed using a hot melt adhesive composition.

[0116] The hot melt adhesive composition may include a commonly known hot melt adhesive. Specifically, the hot melt adhesive may include one or more selected from the group consisting of polyurethane resins, polyester resins, ethylene-vinyl acetate resins, polyamide resins, and polyolefin resins.

[0117] The thickness of the adhesive layer is not particularly limited, and may be, for example, 5 μm to 30 μm, 10 μm to 30 μm, 20 μm to 27 μm, or 23 μm to 25 μm. When the thickness of the adhesive layer satisfies the above range, the bonding strength between the polishing layer and the support layer can be ensured at a constant level.

[0118] The support layer is provided under the polishing layer and serves to stably support the polishing layer while absorbing and / or dispersing impacts applied to the polishing layer. Such a support layer may be manufactured (formed) using a nonwoven fabric, suede, or a porous pad.

[0119] The thickness of the support layer is not particularly limited, and may be, for example, 0.5 mm to 4 mm, 0.6 mm to 3.5 mm, 0.8 mm to 3 mm, or 1 mm to 2 mm. The hardness of the support layer is not particularly limited, and may be, for example, 55 Asker C to 90 Asker C, 60 Asker C to 85 Asker C, 65 Asker C to 80 Asker C, or 70 Asker C to 75 Asker C. When the thickness and hardness of the support layer each satisfy the above ranges, the polishing pad can be made lighter while stably supporting the polishing layer.

[0120] <Polishing pad characteristics> The polishing pad according to the above embodiment has excellent characteristics such as polishing rate in the CMP process. For example, the removal rate of a CMP process for a silicon oxide film, more specifically, when a silicon oxide film of a silicon wafer is polished with a ceria slurry using the polishing pad, may be 2500 Å / min or more, 3000 Å / min or more, 3500 Å / min or more, or 3600 Å / min or more, and may be 5000 Å / min or less, 4700 Å / min or less, 4500 Å / min or less, or 4200 Å / min or less.

[0121] As a specific example, when a silicon oxide film of a silicon wafer is polished with a ceria slurry using the polishing pad, the polishing rate according to the following formula may be 3500 Å / min to 4700 Å / min, 3500 Å / min to 4500 Å / min, 3500 Å / min to 4200 Å / min, 3900 Å / min to 4400 Å / min, 3900 Å / min to 4250 Å / min, or 3950 Å / min to 4200 Å / min. Polishing rate (Å / min) = Change in film thickness before and after polishing (Å) / Polishing time (min)

[0122] Specifically, the polishing rate may be a polishing rate for a silicon wafer having a diameter of 300 mm on which silicon oxide is deposited. The polishing rate may be measured under conditions of a polishing load of 4.0 psi, a polishing pad rotation speed of 150 rpm, and a calcined ceria slurry being fed at 250 mL / min while rotating a platen at 150 rpm for 60 seconds. The temperature condition during the measurement of the polishing rate is not particularly limited, and may be, for example, room temperature.

[0123] The pad cut rate of the polishing layer may be 25 μm / hr or more, 30 μm / hr or more, 35 μm / hr or more, or 38 μm / hr or more, and 50 μm / hr or less, 45 μm / hr or less, or 42 μm / hr or less. As a specific example, the polishing pad cut rate at a conditioning pressure of 6 lbf and a rotation speed of 100 to 110 rpm, i.e., the pad cut rate of the polishing layer, may be 25 μm / hr to 50 μm / hr, 30 μm / hr to 50 μm / hr, or 38 μm / hr to 48.5 μm / hr.

[0124] In one embodiment, the polishing pad may have a CMP process polishing rate (Å / min) of 3900 Å / min to 4400 Å / min and a polishing pad removal rate (μm / hr) of 38 μm / hr to 45 μm / hr.

[0125] In another embodiment, the polishing pad may have a CMP process polishing rate (Å / min) of 3500 Å / min to 4700 Å / min and a polishing pad removal rate (μm / hr) of 30 μm / hr to 50 μm / hr.

[0126] The polishing pad may have a compression rate (%) of 0.3% to 1.8%, 0.4% to 1.6%, 0.5% to 1.5%, 0.6% to 1.4%, or 0.8% to 1.3%.

[0127] The polishing pad according to the embodiment can be excellent in environmental friendliness because the polishing layer is manufactured from a biomass-containing composition. In addition, the polishing pad according to the embodiment can have physical properties required in the CMP process by adjusting the polymer components contained in the biomass-containing composition used to manufacture the polishing layer, more specifically, the components and contents of the bio-based polymer polyol and the bio-based monomer polyol in the polymer components, and can have excellent polishing rate, cutting rate, etc.

[0128] For example, the polishing pad according to the embodiment may have a biomass content of 1% to 50% by weight based on the total weight of the polishing pad. For example, based on the total weight of the polishing pad, the total biomass content of the polishing pad may be 2% to 50% by weight, 3% to 50% by weight, 4% to 50% by weight, 5% to 50% by weight, 6% to 50% by weight, 7% to 50% by weight, 8% to 50% by weight, 2% to 45% by weight, 3% to 42% by weight, 4% to 38% by weight, 4.5% to 36% by weight, 5% to 34% by weight, 8% to 32% by weight, 15% to 33% by weight, or 25% to 32% by weight.

[0129] [Polishing pad manufacturing method] According to yet another embodiment, a method for producing a polishing pad is provided, comprising the steps of preparing a urethane prepolymer comprising a polyol and a polyisocyanate, and curing the urethane prepolymer to produce a polishing layer comprising a polyurethane resin, wherein the polyol comprises a bio-based polymer polyol.

[0130] Another embodiment of a method for manufacturing a polishing pad includes preparing a bio-based urethane prepolymer using a polyurethane resin including a polyol component and a polyisocyanate component, and curing the bio-based urethane prepolymer to produce a polishing layer, the polyol component including a bio-based polymer polyol and a bio-based monomer polyol.

[0131] Thereby, the polishing pad can have a polishing layer formed of a cured urethane prepolymer containing the bio-based polymer polyol and the bio-based monomer polyol.

[0132] First, a urethane prepolymer containing a polyol component and a polyisocyanate component is prepared. Specifically, a composition containing the polyol component containing the bio-based polymer polyol and the bio-based monomer polyol and the polyisocyanate is put into a reactor and prepolymerized to prepare a urethane prepolymer. The reaction conditions are not particularly limited, but the reaction temperature may be 70°C to 90°C or 75°C to 85°C, and the reaction time may be 1 hour to 4 hours, or 2 hours to 3 hours.

[0133] The explanations regarding the polyol and the polyisocyanate given as examples in the polishing pad can be applied similarly to the explanations regarding the polyol and the polyisocyanate.

[0134] In addition, in reacting the polyol component (z) with the polyisocyanate component (w), the reaction ratio (z:w) is not particularly limited, but taking into consideration the overall physical properties of the polishing layer, it may be a weight ratio of 1:2-14, a weight ratio of 1:3-12, a weight ratio of 1:4-10, or a weight ratio of 1:5-8.

[0135] The biomass-containing urethane prepolymer obtained by the reaction of such a polyol component with a polyisocyanate may have a biomass content of 4% by weight to 80% by weight. For example, the biomass content of the biomass-containing urethane prepolymer may be 4% by weight to 78% by weight, 7% by weight to 76% by weight, 8% by weight to 74% by weight, 9% by weight to 72% by weight, 10% by weight to 69% by weight, 25% by weight to 67% by weight, or 45% by weight to 65% by weight, based on the total weight of the biomass-containing urethane prepolymer.

[0136] The biomass-containing urethane prepolymer may have a weight average molecular weight of 500 g / mol to 1500 g / mol. For example, the weight average molecular weight of the biomass-containing urethane prepolymer may be 600 g / mol to 1400 g / mol, 700 g / mol to 1300 g / mol, or 800 g / mol to 1200 g / mol.

[0137] The biomass-containing urethane prepolymer may have a terminal NCO content (NCO%) of 6 to 14% by weight. For example, the terminal NCO content (NCO%) of the biomass-containing urethane prepolymer may be 6.5 to 13% by weight, 7 to 12% by weight, 7.5 to 11% by weight, or 8 to 10% by weight. When the weight average molecular weight and NCO% of the biomass-containing urethane prepolymer each satisfy the above range, a polishing pad with a superior polishing rate in the CMP process can be provided.

[0138] The biomass-containing urethane prepolymer can then be cured to produce an abrasive layer. Specifically, the bio-based urethane prepolymer can be cured to produce an abrasive layer comprising a polyurethane resin.

[0139] More specifically, the biomass-containing urethane prepolymer may be mixed with a curing agent, a foaming agent, a surfactant, a reaction rate regulator, etc., and then cast to obtain a molded product, which may then be cut to produce an abrasive layer.

[0140] For this purpose, the polyurethane resin can be prepared by filling the urethane prepolymer, the curing agent, the foaming agent, etc. into each injection line and mixing them. Specifically, the mixing can be performed at a speed of 1000 rpm to 10000 rpm, 2500 rpm to 8500 rpm, or 4000 rpm to 7000 rpm. The foaming agent can be mixed through an injection line separate from the biomass-containing urethane prepolymer injection line, or can be premixed with the biomass-containing urethane prepolymer before the biomass-containing urethane prepolymer is filled into the injection line.

[0141] The curing agent is as described above, and the content of the curing agent may be 15 to 55 parts by weight, 20 to 50 parts by weight, 25 to 45 parts by weight, or 30 to 40 parts by weight relative to 100 parts by weight of the urethane prepolymer. By having the content of the curing agent satisfy the above range, it may be more advantageous to realize a polishing pad with excellent physical properties.

[0142] The reaction ratio (curing reaction ratio) of the urethane prepolymer and the curing agent is not particularly limited, and may be, for example, an equivalent ratio of 1:0.5 to 1.3, an equivalent ratio of 1:0.6 to 1.2, an equivalent ratio of 1:0.7 to 1.1, or an equivalent ratio of 1:0.8 to 1. By carrying out the curing reaction at the reaction ratio, the curing reaction is optimized, and a polishing pad having physical properties (hardness, modulus, etc.) required in the CMP process can be provided.

[0143] The foaming agent may be, for example, a solid-phase foaming agent. The content of the solid-phase foaming agent is 0.5 parts by weight to 10 parts by weight, specifically 0.7 parts by weight to 8 parts by weight, 0.9 parts by weight to 6 parts by weight, or 1 part by weight to 5 parts by weight, relative to 100 parts by weight of the biomass-containing urethane prepolymer. The content of the solid-phase foaming agent satisfies the above range, which is more advantageous in realizing a polishing pad with excellent physical properties.

[0144] The surfactant is not particularly limited, but specifically may be a silicone-based surfactant.

[0145] The reaction rate regulator is not particularly limited, and specifically may include one or more selected from the group consisting of triethylenediamine, dimethylethanolamine, tetramethylbutanediamine, 2-methyl-triethylenediamine, dimethylcyclohexylamine, triethylamine, triisopropanolamine, 1,4-diazabicyclo(2,2,2)octane, bis(2-methylaminoethyl)ether, trimethylaminoethylethanolamine, N,N,N',N'',N''-pentamethyldiethyldimethylaminoethylamine, dimethylaminopropylamine, benzyldimethylamine, N-ethylmorpholine, N,N-dimethylaminoethylmorpholine, N,N-dimethylcyclohexylamine, 2-methyl-2-azanorbornene, dibutyltin dilaurate, stannous octoate, dibutyltin diacetate, dioctyltin diacetate, dibutyltin maleate, dibutyltin di-2-ethylhexanoate, and dibutyltin dimercaptide.

[0146] The step of preparing the polishing layer may include a process of pouring the composition in which the urethane prepolymer, the curing agent, and the foaming agent are mixed into a mold and curing the composition. The curing reaction conditions are not particularly limited, but the curing reaction temperature is 60° C. to 130° C. or 75° C. to 110° C., and the mold pressure is 50 kg / m. 2 ~260kg / m 2 or 80kg / m 2 ~180kg / m 2 It could be.

[0147] The method for manufacturing a polishing pad according to the embodiment may further include a step of manufacturing an adhesive layer and a support layer after manufacturing the polishing layer. In addition, it may further include a step of cutting the surface of the polishing layer, a step of processing a groove on the surface of the polishing layer, a polishing pad inspection step, a polishing pad packaging step, etc., and these steps may be applied to a conventional method for manufacturing a polishing pad.

[0148] [Chemical mechanical polishing (CMP)] A polishing pad according to the above embodiment may be used to manufacture semiconductor devices by chemical mechanical polishing. According to an embodiment, a method for manufacturing a semiconductor device includes polishing a surface of a semiconductor substrate using a polishing pad. Specifically, the method may include providing a polishing pad according to the embodiment, and polishing the surface of the semiconductor substrate by rotating the polishing pad relative to the polishing surface of the polishing layer and the surface of the semiconductor substrate so that the polishing surface of the polishing pad and the surface of the semiconductor substrate contact each other.

[0149] FIG. 4 illustrates a process for manufacturing a semiconductor device using a polishing pad according to an embodiment. Referring to FIG. 4, the polishing pad 100 according to the embodiment is mounted on a platen 200, and then a semiconductor substrate 600 to be polished is placed on the polishing pad 100. At this time, the surface to be polished of the semiconductor substrate 600 directly contacts the polishing surface of the polishing pad 100. For polishing, a polishing slurry 400 may be sprayed onto the polishing pad through a nozzle. Then, the semiconductor substrate 600 and the polishing pad 100 rotate relative to each other to polish the surface of the semiconductor substrate 600. At this time, the rotating direction of the semiconductor substrate 600 and the rotating direction of the polishing pad 100 may be the same direction or opposite directions. The semiconductor substrate 600 may be pressed against the polishing surface of the polishing pad 100 with a predetermined load while being mounted on a polishing head 510, and then the surface of the semiconductor substrate 600 may be polished. In addition, the method for manufacturing a semiconductor device may further include a step of processing the polishing surface of the polishing pad 100 with a conditioner 470 simultaneously with polishing the semiconductor substrate 600 in order to maintain the polishing surface of the polishing pad 100 in a state suitable for polishing.

[0150] (Example) The above contents will be explained in more detail with reference to the following examples, however, the following examples are intended to illustrate the present invention and are not intended to limit the scope of the present invention.

[0151] [material] The bio-based polyols used in the examples and comparative examples are as follows: -ECOTRION H1000: SK Chemicals, polytrimethylene ether glycol, molecular weight 1000g / mol, hydroxyl value 102.0mgKOH / g~124.7mgKOH / g, biomass content 100% by weight -Sovermol 1102: BASF, molecular weight 512 g / mol, hydroxyl value 230 mg KOH / g, biomass content 80% to 100% by weight - Priplast 1838: Croda, molecular weight 2000 g / mol, hydroxyl value 52 mg KOH / g to 60 mg KOH / g, biomass content 82% by weight -Bio-based 1,3-propanediol: molecular weight 76 g / mol, biomass content 100 wt%

[0152] (Example 1-1) Step 1: Bio-based urethane prepolymer preparation 35g of toluene diisocyanate (TDI), 5g of 4,4'-methylenedicyclohexyl diisocyanate (H12MDI), 60g of bio-based polymer polyol (ECOTRION H1000), and 5g of diethylene glycol (DEG) were placed in a four-neck flask and reacted at 80°C for 3 hours to prepare a bio-based urethane prepolymer with an NCO content of approximately 9% by weight.

[0153] Step 2: Polishing layer production In a casting machine equipped with an inert gas injection line, the prepolymer tank was filled with the bio-based urethane prepolymer prepared in step 1, and the hardener tank was filled with bis(4-amino-3-chlorophenyl)methane (Ishihara Chemical Co., Ltd.), and nitrogen (N2) was used as an inert gas. Meanwhile, 1 part by weight of a solid phase foaming agent (Akzonobel Co., Ltd.) and 1 part by weight of a silicone surfactant (Evonik Co., Ltd.) were added to 100 parts by weight of the urethane prepolymer through separate lines to be mixed with the urethane prepolymer. Each raw material was added to the mixing head at a constant speed through each input line and stirred. At this time, the urethane prepolymer and the hardener were added in an equivalent ratio of 1:1, and nitrogen (N2), an inert gas, was injected at a rate of 0.5 L / min to 1.5 L / min. The stirred raw material was discharged at a discharge rate of 10 kg / min into a mold (1000 mm x 1000 mm x 3 mm) preheated to 80°C, and then cast at 120°C to obtain a molded body. Then, the upper and lower ends of the molded body were cut to a thickness of 0.5 mm each to obtain a polishing layer (top pad layer) with a thickness of 2 mm (specific gravity 0.82 g / cc, average pore size 23.6 μm).

[0154] Phase 3: Polishing pad manufacturing A support layer (subpad) having a thickness of 1.1 mm was prepared by impregnating a polyester fiber nonwoven fabric with a polyurethane resin. Then, the polishing layer prepared in step 2 was bonded to the support layer using a hot melt adhesive to prepare a polishing pad (thickness: 3.32 mm) having a structure of polishing layer / adhesive layer / support layer.

[0155] (Example 1-2) 35g of toluene diisocyanate (TDI), 5g of 4,4'-methylenedicyclohexyl diisocyanate (H12MDI), 50g of bio-based polymer polyol (ECOTRION H1000), and 5g of bio-based 1,3-propanediol (1,3-PDO) were added to a four-neck flask and reacted at 80°C for 3 hours to prepare a bio-based urethane prepolymer with an NCO% of approximately 9% by weight.

[0156] Using the prepared urethane prepolymer, a polishing pad (thickness: 3.32 mm) having a structure of a polishing layer / adhesive layer / support layer was manufactured through the same process as in steps 2 and 3 of Example 1-1.

[0157] (Examples 1-3) 35g of toluene diisocyanate (TDI), 5g of 4,4'-methylenedicyclohexyl diisocyanate (H12MDI), and 60g of bio-based polymer polyol (Sovermol 1102) were added to a four-neck flask and reacted at 80°C for 3 hours to prepare a bio-based urethane prepolymer with an NCO content of approximately 9% by weight.

[0158] Using the prepared urethane prepolymer, a polishing pad (thickness: 3.32 mm) having a structure of a polishing layer / adhesive layer / support layer was manufactured through the same process as in steps 2 and 3 of Example 1-1.

[0159] (Examples 1 to 4) 35g of toluene diisocyanate (TDI), 5g of 4,4'-methylenedicyclohexyl diisocyanate (H12MDI), 50g of bio-based polymer polyol (Priplast 1838), and 10g of bio-based 1,3-propanediol (1,3-PDO) were added to a four-neck flask and reacted at 80°C for 3 hours to prepare a bio-based urethane prepolymer with an NCO content of approximately 9% by weight.

[0160] Using the prepared urethane prepolymer, a polishing pad (thickness: 3.32 mm) having a structure of a polishing layer / adhesive layer / support layer was manufactured through the same process as in steps 2 and 3 of Example 1-1.

[0161] (Comparative Example 1-1) 35 g of toluene diisocyanate (TDI), 5 g of 4,4'-methylenedicyclohexyl diisocyanate (H12MDI), 60 g of polytetramethylene ether glycol (PTMEG), and 5 g of diethylene glycol (DEG) were added to a four-neck flask and reacted at 80°C for 3 hours to prepare a biomass-free urethane prepolymer with an NCO% of approximately 9% by weight.

[0162] Using the prepared urethane prepolymer, a polishing pad (thickness: 3.32 mm) having a structure of a polishing layer / adhesive layer / support layer was manufactured through the same process as in steps 2 and 3 of Example 1-1.

[0163] In the above examples and comparative examples, the types and amounts of raw materials used to prepare the urethane prepolymers are summarized in Tables 1 and 2 below.

[0164] JPEG2025029573000002.jpg79161

[0165] JPEG2025029573000003.jpg109165

[0166] (Experimental Example 1-1: Characteristics of polishing pad) (1)Hardness The polishing layer (thickness: 2 mm, length: 5 cm, width: 5 cm) and the support layer (thickness: 1.1 mm, length: 5 cm, width: 5 cm) were each stored at 25°C for 12 hours, and then the Shore D hardness and Asker C hardness were measured using a hardness tester.

[0167] (2) Tensile strength The polishing layer (thickness: 2 mm, length: 1 cm, width: 4 cm) was subjected to a tensile test at a speed of 50 mm / min using a universal testing meter (UTM) to measure the maximum strength value just before fracture.

[0168] (3) Growth rate The polishing layer (thickness: 2 mm, length: 1 cm, width: 4 cm) was subjected to a tensile test at a speed of 50 mm / min using a universal testing meter (UTM) to measure the maximum deformation length just before fracture, and then the percentage (%) of the ratio of the maximum deformation length to the initial length was calculated.

[0169] (4) Compression ratio A dial thickness gauge (129-E, YASUDA) was used to measure the thickness of an abrasive pad (thickness: 3.32 mm, length: 25 mm, width: 25 mm). The change in thickness (A) was measured after placing an 85 g weight on the pad for 30 seconds, and the change in thickness (B) was measured after placing an additional 800 g weight (85 g weight + 800 g weight) on the pad for 3 minutes. This change was used as the compression ratio. Compression ratio = [(AB) / A] x 100 The results are summarized in Table 3 below.

[0170] JPEG2025029573000004.jpg117162

[0171] As can be seen from Table 3, Examples 1-1 to 1-4 using bio-based polymer polyol were generally good in terms of characteristics. In particular, in the case of Examples 1-1 and 1-2 using bio-based polyether polyol, the characteristics are almost similar to those of Comparative Example 1 using petroleum-based polymer polyol, and it can be confirmed that they have physical properties at the same level as conventional polishing pads while being environmentally friendly.

[0172] (Experimental Example 1-2: Performance of Polishing Pad) (1) Polishing rate A polishing pad was fixed on the platen of a CMP device, and the silicon oxide film of a silicon wafer (diameter: 300 mm) was set underneath to perform the CMP process. Specifically, the polishing load was adjusted to 4.0 psi, and the platen was rotated at 150 rpm for 60 seconds while the calcined ceria slurry was fed onto the polishing pad at a rate of 250 mL / min, to polish the silicon oxide film. After polishing, the silicon wafer was removed from the carrier, attached to a spin dryer, washed with purified water, and then dried with nitrogen for 15 seconds. The thickness difference of the silicon oxide film before and after polishing of the dried silicon wafer was measured using a spectroscopic interference thickness measuring instrument (SI-F80R, Kyence). The polishing rate was calculated according to the following formula. Polishing rate (Å / min) = Change in film thickness before and after polishing (Å) / Polishing time (min)

[0173] (2) Polishing pad cutting rate The polishing pad was preconditioned with deionized water for the first 10 minutes, then conditioned again by spraying deionized water for 1 hour, and the thickness change of the polishing pad was measured. In this case, a CTS AP-300HM device was used for conditioning, and a Sasol LPX-DS2 disk was used. The conditioning pressure was 6 lbf, and the rotation speed was 100 rpm to 110 rpm. The results are summarized in Table 4 below.

[0174] JPEG2025029573000005.jpg43154

[0175] As can be seen from Table 4, Examples 1-1 to 1-4 using bio-based polymer polyol were generally good in terms of performance. In particular, in the case of Examples 1-1 and 1-2 using bio-based polyether polyol, the polishing rate and cutting rate are almost similar to those of Comparative Example 1 using petroleum-based polymer polyol, and it can be confirmed that they have environmental friendliness while also having the same level of performance as conventional polishing pads.

[0176] (Experimental Example 1-3: 13C-NMR spectrum) For each of the polishing layers in the Examples and Comparative Examples, 1 g of the polishing layer and 15 mL of a 0.3 M potassium hydroxide (KOH) aqueous solution were placed in a sealed container having a capacity of 48 mL, and reacted for 48 hours under a temperature condition of 150° C. to prepare a test composition. 5 mg of the test composition was dissolved in CDCl3, and the composition was analyzed at room temperature using a nuclear magnetic resonance (NMR) device (JEOL 500 MHz, 90° pulse). 13 C-NMR analysis was carried out. The results are shown in the following Tables 5 to 7. Furthermore, peaks 1 to 3 are shown in FIG. 1, and peaks 4 and 5 are shown in FIG.

[0177] JPEG2025029573000006.jpg41133

[0178] JPEG2025029573000007.jpg5090

[0179] JPEG2025029573000008.jpg54164

[0180] As can be seen from Table 7, the polishing layers produced in some of the examples 13 In the C-NMR spectrum, some or all of peaks 1 to 5 were observed. When this is combined with the results of Experimental Examples 1 and 2, it can be confirmed that the presence or absence of peaks 1 to 5 is related to the characteristics and performance of the polishing pad.

[0181] (Example 2-1) Step 1: Bio-based urethane prepolymer preparation Into a four-neck flask, 35 g of toluene diisocyanate (TDI), 5 g of 4,4'-methylenedicyclohexyl diisocyanate (H12MDI), 50 g of bio-based polymer polyol (polytrimethylene ether glycol, product name: ECOTRION H1000, SK Chemicals, molecular weight: 1000 g / mol, hydroxyl value: 102.0 mg KOH / g to 124.7 mg KOH / g, biomass content: 100% by weight), and 5 g of bio-based 1,3-propanediol (molecular weight: 76 g / mol, biomass content: 100% by weight) were added, and the mixture was reacted at 80°C for 3 hours to prepare a bio-based urethane prepolymer with an NCO% of 8% by weight to 12% by weight.

[0182] Step 2: Polishing layer production In a casting machine equipped with an inert gas injection line, the prepolymer tank was filled with the bio-based urethane prepolymer prepared in step 1, the hardener tank was filled with bis(4-amino-3-chlorophenyl)methane (Ishihara Chemical Co., Ltd.), and nitrogen (N2) was used as the inert gas. In addition, 1 part by weight of a solid phase foaming agent (Akzonobel Co., Ltd.) and 1 part by weight of a silicone surfactant (Evonik Co., Ltd.) were added to 100 parts by weight of the urethane prepolymer through separate lines to be mixed with the urethane prepolymer. Each raw material was added to the mixing head at a constant speed through each input line and stirred.

[0183] At this time, the urethane prepolymer and the curing agent were charged in an equivalent ratio of 1:1, and nitrogen (N2), an inert gas, was injected at a rate of 0.5 L / min to 1.5 L / min. The stirred raw material was injected at a discharge rate of 10 kg / min into a mold (length: 1000 mm, width: 1000 mm, height: 3 mm) preheated to 80°C, and cast at 120°C to obtain a molded body. Then, the upper and lower ends of the molded body were cut to a thickness of 0.5 mm each to obtain a polishing layer (top pad layer) with a thickness of 2 mm (specific gravity 0.82 g / cc, average pore size 23.6 μm).

[0184] Phase 3: Polishing pad manufacturing A support layer (subpad) having a thickness of 1.1 mm was prepared by impregnating a polyester fiber nonwoven fabric with a polyurethane resin. Then, the polishing layer prepared in step 2 was bonded to the support layer using a hot melt adhesive to prepare a polishing pad (thickness: 3.32 mm) having a structure of polishing layer / adhesive layer / support layer.

[0185] (Comparative Example 2-1) A polishing pad was prepared in the same manner as in Example 2-1, except that in step 1, ethylene glycol was used instead of bio-based 1,3-propanediol, and 10 g of 4,4'-methylenedicyclohexyl diisocyanate (H12MDI) was used.

[0186] (Comparative Example 2-2) A polishing pad was prepared in the same manner as in Example 2-1, except that in step 1, 1,4-butanediol was used instead of bio-based 1,3-propanediol, and 55 g of biopolymer polyol was used.

[0187] (Comparative Example 2-3) A polishing pad was prepared in the same manner as in Example 2-1, except that in step 1, 30 g of toluene diisocyanate (TDI), 5 g of 4,4'-methylenedicyclohexyl diisocyanate (H12MDI), 55 g of biopolymer polyol, and 5 g of 1,6-hexanediol were used.

[0188] (Experimental Example 2-1: Hardness) The hardness of the polishing layer and the support layer of the polishing pads manufactured in Example 2-1 and Comparative Examples 2-1 to 2-3 was measured. Specifically, the polishing layer (thickness: 2 mm, length: 5 cm, width: 5 cm) and the support layer (thickness: 1.1 mm, length: 5 cm, width: 5 cm) were each stored at 25°C for 12 hours, and then the Shore D hardness and the Asker C hardness were measured using a hardness tester.

[0189] (Experimental Example 2-2: Tensile strength) The tensile strength of the polishing layer of the polishing pads manufactured in Example 2-1 and Comparative Examples 2-1 to 2-3 was measured. Specifically, the polishing layer (thickness: 2 mm, length: 1 cm, width: 4 cm) was subjected to a tensile test at a speed of 50 mm / min using a universal testing meter (UTM) to measure the maximum strength value just before breakage.

[0190] (Experimental Example 2-3: Elongation) The elongation of the polishing layer of the polishing pads manufactured in Example 2-1 and Comparative Examples 2-1 to 2-3 was measured. Specifically, the maximum deformation length just before breakage was measured in a tensile test at a speed of 50 mm / min using a universal testing meter (UTM) for the polishing layer (thickness: 2 mm, length: 1 cm, width: 4 cm), and the percentage (%) of the maximum deformation length relative to the initial length was calculated.

[0191] (Experimental Example 2-4: Compression ratio) The compression ratio of the polishing pads manufactured in Example 2-1 and Comparative Examples 2-1 to 2-3 was measured. Specifically, a dial thickness gauge (129-E, YASUDA) was used for a polishing pad (thickness: 3.32 mm, length: 25 mm, width: 25 mm) to measure the thickness (A) after placing an 85 g weight for 30 seconds, and the thickness (B) after placing an additional 800 g weight (85 g weight + 800 g weight) for 3 minutes, and the change in thickness was calculated to obtain the compression ratio. Compression ratio = [(AB) / A] x 100

[0192] JPEG2025029573000009.jpg106161

[0193] As can be seen from Table 8, it was confirmed that the polishing pad of Example 2-1, which uses a bio-based polymer polyol and a bio-based monomer polyol together, has environmental friendliness while exhibiting physical properties equal to or better than conventional petroleum-based polishing pads.

[0194] (Experimental Example 2-5: Polishing rate) For the polishing pads manufactured in Example 2-1 and Comparative Examples 2-1 to 2-3, the polishing pads were fixed onto the platen of a CMP device, and a silicon oxide film of a silicon wafer (diameter: 300 mm) was placed underneath to perform the CMP process, and the polishing rate was measured.

[0195] Specifically, the polishing load was adjusted to 4.0 psi, and the calcined ceria slurry was fed onto the polishing pad at a rate of 250 mL / min while rotating the platen at 150 rpm for 60 seconds to polish the silicon oxide film. After polishing, the silicon wafer was removed from the carrier, attached to a rotary dehydrator, washed with purified water, and then dried with nitrogen for 15 seconds. The thickness difference of the silicon oxide film before and after polishing of the dried silicon wafer was measured using a spectroscopic interference thickness measuring device (SI-F80R, Kyence Co., Ltd.), and the polishing rate was calculated according to the following formula. Polishing rate (Å / min) = Change in film thickness before and after polishing (Å) / Polishing time (min)

[0196] (Experimental Example 2-6: Cutting rate) The removal rate of the polishing pads manufactured in Example 2-1 and Comparative Examples 2-1 to 2-3 was measured. Specifically, the polishing pad was preconditioned with deionized water for the first 10 minutes, and then conditioned again by spraying deionized water for 1 hour, and the thickness change of the polishing pad was measured. In this case, a CTS AP-300HM device was used for conditioning, and a Sasol LPX-DS2 disk was used. The conditioning pressure was 6 lbf, and the rotation speed was 100 rpm to 110 rpm.

[0197] JPEG2025029573000010.jpg43134

[0198] As can be seen from Table 9, the polishing pad of Example 2-1, which uses both bio-based polymer polyol and bio-based monomer polyol, was confirmed to have physical properties equal to or better than those of conventional petroleum-based polishing pads while being environmentally friendly. More specifically, the polishing pad of Example 2-1 was evaluated to have excellent polishing rate and cutting rate while being environmentally friendly by appropriately controlling physical properties such as hardness, tensile strength and elongation along with the biomass content. [Explanation of symbols]

[0199] 1:Peak 1 2: Peak 2 3: Peak 3 4: Peak 4 5: Peak 5 10: Polishing layer 20: Adhesive layer 30:Support layer 100: Polishing pad 200: Platen 300: Conditioner 400: Abrasive slurry 510: Polishing head 520: Career 600: Semiconductor substrate (wafer)

Claims

1. Includes an abrasive layer, The polishing layer contains a polyurethane resin, The polyurethane resin contains a polyol and a polyisocyanate, The polishing pad, wherein the polyol comprises a bio-based polymer polyol.

2. The bio-based polymer polyol is The molecular weight is 400 g / mol to 3000 g / mol, The hydroxyl value (OH-value) is 35 mg KOH / g to 250 mg KOH / g, The biomass content is 20% to 100% by weight; 2. The polishing pad according to claim 1, wherein the functionality is 2 to 4.

3. The bio-based polymer polyol is 10. The polishing pad of claim 1, comprising one or more selected from the group consisting of bio-based polyether polyols, bio-based polyester polyols, bio-based polycarbonate polyols, and bio-based polycaprolactam polyols.

4. The polyurethane resin is further comprising one or more bio-based monomer polyols; 2. The polishing pad according to claim 1, wherein the weight ratio of the bio-based polymer polyol to the bio-based monomer polyol is 5-20:0.01-2.

5. The bio-based monomer polyol is The polishing pad of claim 4, comprising one or more selected from the group consisting of bio-based 1,3-propanediol, bio-based 1,3-butanediol, bio-based 1,4-butanediol, bio-based 2,3-butanediol, bio-based 1,5-pentanediol, bio-based 1,9-nonanediol, bio-based 1,10-decanediol, and bio-based isosorbide.

6. The bio-based monomer polyol is The biomass content is 50% by weight or more, The hydroxyl value is 50 mgKOH / g to 200 mgKOH / g, 5. The polishing pad according to claim 4, wherein the weight average molecular weight is from 50 g / mol to 200 g / mol.

7. 1 g of the polishing layer was placed in a 0.3 M potassium hydroxide (KOH) aqueous solution and reacted in a sealed container at 150° C. for 48 hours to obtain a test composition. 13 When the C-NMR spectrum was measured, A first peak appears at 28 ppm to 31 ppm; A second peak appears at 31 ppm to 33 ppm; and a third peak appearing at 67 ppm to 71 ppm.

8. a ratio of the area of ​​the first peak to the area of ​​the second peak is 4.4 to 5.7; 8. The polishing pad according to claim 7, wherein the ratio of the area of ​​the third peak to the area of ​​the second peak is 8.2 to 8.

8.

9. A fourth peak appears at 33 ppm to 36 ppm; and A fifth peak appears at 61 ppm to 63 ppm; 8. The polishing pad according to claim 7, wherein the ratio of the area of ​​the fourth peak to the area of ​​the fifth peak is 2.1 to 6.

4.

10. The polishing pad according to claim 1, wherein the polyisocyanate comprises at least one selected from the group consisting of toluene diisocyanate (TDI), naphthalene-1,5-diisocyanate, p-phenylene diisocyanate, tolidine diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate, 4,4'-methylenedicyclohexyl diisocyanate (H12MDI), and isophorone diisocyanate.

11. The polishing layer is Hardness is 45 Shore D to 70 Shore D, Tensile strength is 15N / mm 2 ~27N / mm 2 and 2. The polishing pad according to claim 1, wherein the elongation is from 50% to 150%.

12. The polishing pad is The CMP process polishing rate (Å / min) is 3500 Å / min to 4700 Å / min; 2. The polishing pad according to claim 1, wherein the polishing pad cut rate (μm / hr) is 30 μm / hr to 50 μm / hr.

13. preparing a urethane prepolymer comprising a polyol and an isocyanate; and curing the urethane prepolymer to produce a polishing layer comprising a polyurethane resin. The method for producing a polishing pad, wherein the polyol comprises a bio-based polymer polyol.

14. The method for producing a polishing pad according to claim 13 , wherein the polyol comprises a bio-based polymer polyol and a bio-based monomer polyol.

Citation Information

Patent Citations

  • Alloy fiber

    JP2009079318A

  • Polyurethane for synthetic leather

    JP2018127758A

  • Polishing pad, process for preparing the same, and process for preparing semiconductor device using the same

    JP2021070152A

  • Polyurethane resin composition, film, and artificial leather

    JP2021195376A

  • Polishing pad and manufacturing method of semiconductor device using the same

    JP2022044583A